Cognitive Behavioural Therapy Based Parent Trainings: A Theoretical Review - Gokce Cokamay Yilmaz (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Appropriate parenting skills are crucial for both childs development and mental health. Parent training programs provide this support to parents. Parent training programs, which are based on different approaches have been conducted in the world. When investigating the parent training programs which are proved to be effective on parents and children, parent training programs based on Cognitive Behavioural Therapy (CBT) or the programs which are developed by using the techniques of this approach are seemed to have a significant role. Researches show that these programs are effective on the variables such as parent and child mental health, parenting competence, parenting stress, childs peer relationships and family functioning. Moreover, Dialectical Behaviour Therapy (DBT), Acceptance and Commitment Therapy (ACT) and mindfulness-based approaches which are known as third wave have been added in CBT theories especially in last twenty years. It has been seen that, these approaches were effective in interventions and used in parenting interventions at the same time. Besides, parent training programs, which is developed on the theories those of mentioned, focus on general parenting skills, they are also developed particularly for the parents whose children show the certain problems. The purpose of this literature review is to introduce those evidence-based implementations. Results were discussed in the context of parent training programs and dissemination process of them which are conducted in Turkey. [JCBPR 2018; 7(3.000): 133-143]